Carbon-Based Nanomaterials as Sustainable Noble-Metal-Free Electrocatalysts - Meng, Yuying; Huang, Xiaoqing; Lin, Huaijun; Zhang, Peng; Gao, Qingsheng; Li, Wei (Frontiers in Chemistry, 2019)
Nowadays, due to the worldwide growth demand of energy, over consumption of fossil fuel as well as their accompanying increased negative environmental impacts, the development of renewable energy systems, such as fuel cells and water electrolyzers, is becoming one of the “holy grail” for researchers. However, their large-scale applications have been severely limited by precious and unsustainable noble-metal electocatalysts. Hence, it is highly desired to develop robust electrocatalysts composed exclusively of low-cost and earth-abundant elements for these energy conversion processes, to reduce or replace the expensive and scarce noble-metals. Carbon-based nanomaterials, including heteroatoms-doped carbons and carbon-encapsulated metal materials, have recently attracted great interests because they show remarkable electrocatalytic performance and long-term stability for energy-related reactions, such as oxygen reduction reaction, hydrogen and oxygen evolution reactions, hydrazine oxidation reaction, etc. This mini review summarizes the recent progress in heteroatoms-doped carbon and carbon-encapsulated metal materials, highlighting the promise as cost-efficient electrocatalysts. Finally, a prospective on the future development of these promising materials is offered.